Immature granulocytes as a sepsis predictor in patients undergoing cardiac surgery. (23rd January 2019) - Porizka, Michal; Volny, Lukas; Kopecky, Petr; Kunstyr, Jan; Waldauf, Petr; Balik, Martin
Abstract: OBJECTIVES: Usefulness of immature granulocyte percentage (IG%) to discriminate between postoperative non-infective systemic inflammatory response syndrome (SIRS) and sepsis was tested in cardiac surgical patients. METHODS: A retrospective analysis of 124 patients who developed non-infective SIRS and sepsis after elective cardiac surgery was performed. Predictive ability of IG% to predict sepsis was compared to procalcitonin (PCT), white blood cell count, temperature and different biomarker combinations using receiver operating characteristic and logistic regression analysis. The optimal cut-off points, diagnosis sensitivity and specificity were calculated. RESULTS: There were 44 patients diagnosed with sepsis and 80 patients with non-infective SIRS. In receiver operating characteristic analysis, area under the curve was higher for IG% (0.71) and PCT (0.72) compared to white blood cell count (0.62) and temperature (0.58). The best cut-off value for IG% was 1.45% (sensitivity 70.5%, specificity 60%) and 1.43  µ g/l for PCT (sensitivity 65.9%, specificity 75%). The combination of IG% and PCT provided the best sepsis prediction (area under the curve of 0.8, sensitivity 63.6% and specificity 88.8%). CONCLUSIONS: In cardiac surgical patients, IG% is a helpful marker with the moderate ability to discriminate between sepsis and non-infective SIRS, comparable to serum PCT. A combination of these parameters increased the test's overall predictive ability by improving its specificity.